Research on the interaction of astragaloside IV and calycosin in Astragalus membranaceus with HMGB1 - Junyi Ye; Yong Huang; Xuewa Jiang; Pingping Shen; Chaofeng Zhang; Jian Zhang (BMC, 2023)
Abstract Background High mobility group box 1 protein (HMGB1), a lethal late inflammatory mediator, contributes to the pathogenesis of diverse inflammatory and infectious diseases. Astragaloside IV and calycosin as active ingredients in Astragalus membranaceus, possess potent regulatory ability on HMGB1-induced inflammation, however, the interaction between these two phytochemicals and HMGB1 has not been elucidated yet. Methods To further investigate the interaction of astragaloside IV, calycosin with HMGB1 protein, surface plasma resonance (SPR) and a series of spectroscopic methods, including UV spectra, fluorescence spectroscopy, circular dichroism (CD), were used. Molecular docking was also carried out to predict the atomic level's binding modes between two components and HMGB1. Results Astragaloside IV and calycosin were found to be able to bind HMGB1 directly and affect the secondary structure and environment of the chromogenic amino acids of HMGB1 to different extents. In silico, astragaloside IV and calycosin showed a synergistic effect by binding to the two independent domains B-box and A-box in HMGB1, respectively, where hydrogen and hydrophobicity bonds were regarded as the crucial forces. Conclusion These findings showed that the interaction of astragaloside IV and calycosin with HMGB1 impaired its proinflammatory cytokines function, providing a new perspective for understanding the mechanism of A. membranaceus in treating aseptic and infectious diseases.